2021
DOI: 10.1016/j.heliyon.2021.e07940
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of growth and yield traits in rice genotypes using multivariate analysis

Abstract: Rice ( Oryza sativa L.) is the first staple crop in terms of production and area of cultivation in Nepal. The amount of genetic variability is important factor in identifying suitable genotypes in rice breeding programs. This study was conducted in Khumaltar, Lalitpur, Nepal during rainy seasons of 2018 and 2019. Forty rice genotypes were planted in Alpha Lattice Design with two replications to determine the genetic diversity among them. The rice genotypes were grouped into 7 clusters ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…Descriptive statistics are applied to analyze the collated data while the hypotheses are decided with the aid of ANOVA analysis. This method is in agreement with the approach of (Ladapo et al, 2020;Shrestha et al, 2021).…”
Section: Data Collection and Analysissupporting
confidence: 86%
“…Descriptive statistics are applied to analyze the collated data while the hypotheses are decided with the aid of ANOVA analysis. This method is in agreement with the approach of (Ladapo et al, 2020;Shrestha et al, 2021).…”
Section: Data Collection and Analysissupporting
confidence: 86%
“…Similarly, Girma, et al [15] reported significant differences among 64 rice genotypes on their days to heading, days to maturity and plant heigh. A significant variation for plant height and panicle length was also reported by Shrestha [25] while studying the variability of 40 rice genotypes. The variability among the newly introduced and tested genotypes was highly significant for their plant height, panicle length and 1000 seed weight were less significant for the measured traits of days to 50% heading and days to 85% maturity.…”
Section: Discussionsupporting
confidence: 59%
“…In this study, except for panicle length, all the parameters showed high heritability values (>80 %), suggesting that these traits can be used as selection criteria for aromatic rice yield improvement [ 43 ]. The success of a crop improvement program depends on the wide genetic variability and high heritability of the traits [ 44 ]. High GCV and PCV for yield and yield-contributing traits of rice were noted by earlier researchers [ [45] , [46] , [47] ] which corroborated the results of the present study.…”
Section: Discussionmentioning
confidence: 99%